Repeatability of Ground Reaction Force Waveforms in Sprint Starts - Aggeloussis Νικόλαος; Methenitis Σπύρος; Gourgoulis Βασίλης; Pilianidis Θεόφιλος; Giannakou Ερασμία (Inquiries in Physical Education and Sport, 2007)
The purpose of this research was to study the repeatability of ground reaction force in sprint starts. Ten athletes, aged between 20 and 24 years, performed 10 successive sprint starts on a starting block. The starting block was located on a piezoelectric force platform which recorded the ground reaction forces at a sampling frequency of 1000Hz. An electrical circuitry served as a trigger to the force platform and functioned with the press of a contact switch that also produced the starting sound. The coefficient of variation (CV) was used to determine the variability of the ground reaction force components between all the trials for each subject. The coefficient of multiple correlation (CMC) was also computed to examine the repeatability of the mean ground reaction waveform for each of its components. The results revealed that the waveforms of the vertical and anterior-posterior components of the ground reaction force showed excellent repeatability in any case. However, the medio-lateral ground reaction force did not always present high repeatability. In conclusion, during the dynamography of a sprint start it issuggested that more than one trial has to be performed and a mean waveform should be calculated for each ground reaction force component, to represent the athlete’s dynamic behavior in each measurement.